Secrets of Rain: An Analytical Perspective in the Holy Quran and Contemporary Sciences : أسرار المطر: نظرة تحليلية في القرآن الكريم والعلوم المعاصرة - Umme Sayma Tajkia (Civilization Research: Journal of Islamic Studies, 2026)
Rainwater is an indispensable element for maintaining life on Earth and ensuring ecological balance. While modern science acknowledges the complex processes of cloud formation and precipitation, the Holy Quran provided detailed descriptions of these phenomena centuries before contemporary discoveries. This research aims to analyze the secrets of rain by comparing Quranic verses with modern scientific findings. It explores the stages of rain formation, the precise measurements governing its descent, and its diverse biological and spiritual benefits. The study employs an analytical and comparative methodology. It examines specific Quranic terminology related to rain types—such as Al-Sayyib, Al-Wabil, and Al-Tall—and correlates them with scientific classifications like convectional, orographic, and cyclonic rainfall. The analysis reveals a precise alignment between the three stages of rain formation described in the Quran (wind movement, cloud accumulation, and precipitation) and modern meteorological stages (evaporation, condensation, and precipitation). Additionally, the study highlights "measured" physical properties, such as how the specific shape of a raindrop prevents it from reaching destructive terminal velocities through atmospheric friction. The research concludes that the scientific miracles within the Quranic text regarding rain affirm its divine origin and its compatibility with contemporary science.